PERAN TERAPI AKUPUNKTUR PADA CARPAL TUNNEL SYNDROME - Wahyuningsih Djaali,*,** Christina Lanny Simadibrata,* Irma Nareswari,* Dwi Rachma Helianthi,* Kemas (NEURONA, 2019)
TUNNEL SYNDROME CTS IS THE MOST COMMON PERIPHERAL NEUROPATHY IN ESTABLISHING A DIAGNOSIS OF CTS IT REQUIRES SEVERAL EXAMINATIONS THAT CANNOT STAND ALONE SYMPTOMS FROM THE ANAMNESIS AND SIGNS OF PHYSICAL EXAMINATION SUCH AS TINEL TEST PHALEN TEST PRESS PROVOCATION EXAMINATION HAND ELEVATION EXAMINATION AND MOTOR EXAMINATION ARE NEEDED NERVE CONDUCTION VELOCITY NCV INVESTIGATION IS ALSO NEEDED TO DIAGNOSE CTS